2020
DOI: 10.1155/2020/8843467
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Career Choice and Attitudes towards Family Medicine in Morocco

Abstract: Background. The motivation of this work is driven on the one hand from the need to understand the medical students’ attitude towards medical training in the context of the reform in Morocco and the creation of “family medicine” as a specialty. This study aims to explore the expectations of medical students regarding family medicine and to identify the factors that may influence setting their choices after graduation. Methods. We conducted a cross-sectional study among Moroccan medical students from public facu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Only 2.9% (n = 12) of those questioned were interested in the role of a primary health care doctor. Studies in other countries also confirm the fact that the professional career of a family physician suffers from a lack of interest [20], although in Georgia, this statistic is much lower. In Egypt, only 4.7% showed any intention to choose this as a future career [21].…”
Section: Discussionmentioning
confidence: 84%
“…Only 2.9% (n = 12) of those questioned were interested in the role of a primary health care doctor. Studies in other countries also confirm the fact that the professional career of a family physician suffers from a lack of interest [20], although in Georgia, this statistic is much lower. In Egypt, only 4.7% showed any intention to choose this as a future career [21].…”
Section: Discussionmentioning
confidence: 84%
“…This is in concordance with a study done in Morocco in 2020. 19 Another study conducted in 2004 by Ward et al 20 concluded that male participants were less likely to become family physicians.…”
Section: Discussionmentioning
confidence: 99%
“…The result of our study showed that, 52.5% of the total population considered radiology as a career, but just 23.1% would choose it as a specialty ( Figure 5 ). Compared to a study in Morocco, none of the medical students considered choosing a career in radiology but the majority of them considered a career in cardiology and general surgery [ 8 ]. We found that, Ghanaian clinical medical students would choose radiology as a career largely because of its scheduling flexibility ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%